2022
DOI: 10.1177/23247096221127792
|View full text |Cite
|
Sign up to set email alerts
|

Small Cell Neuroendocrine of the Head and Neck: A Rare Presentation and Review of the Literature

Abstract: Head and neck tumors account for roughly 3% of malignancies in the United States and about 90% of these tumors are squamous cell cancers. Neuroendocrine neoplasms arise from neural crest cells and are commonly found in the gastrointestinal tract. Neuroendocrine neoplasms arising from the head and neck tend to be rare. In this article, we present a rare case of human papilloma virus–associated poorly differentiated small cell neuroendocrine carcinoma (NEC). Our patient was a 62-year-old African American man who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Additionally, the literature reports the successful use of monoclonal antibodies targeting PD-L1 to treat cases of laryngeal NENs, but this still requires confirmation through large-scale clinical trials. [23]…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the literature reports the successful use of monoclonal antibodies targeting PD-L1 to treat cases of laryngeal NENs, but this still requires confirmation through large-scale clinical trials. [23]…”
Section: Discussionmentioning
confidence: 99%
“…The study concluded that the addition of atezolizumab in the first-line chemotherapy resulted in improved overall and progression-free survival (32). Niforatos et al described the use of atezolizumab with cisplatin and etoposide in a patient with head and neck small cell neuroendocrine cancer with good response (33). Moreover, durvalumab (anti-PD-L1) has been showed to significantly improve overall survival in patients with an extensive stage small cell lung cancer in a recent phase 3 clinical trial (CASPIAN) (34).…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, the improved access to diagnosis by imaging and endoscopy seems to have led to an earlier diagnosis and, therefore, an increase in more localized cases without metastases at the time of detection [ 6 ]. As infrequent entities, references to NEN of the head and neck in the literature include isolated cases or very limited series, most of them referring to NECs [ 4 , 7 ]. While treatment recommendations for this condition are not well established, multidisciplinary interventions, including surgery, chemo, and radiotherapy, are often suggested.…”
Section: Discussionmentioning
confidence: 99%
“…As infrequent entities, references to NEN of the head and neck in the literature include isolated cases or very limited series, most of them referring to NECs [4,7]. While treatment recommendations for this condition are not well established, multidisciplinary interventions, including surgery, chemo, and radiotherapy, are often suggested.…”
Section: Discussionmentioning
confidence: 99%